Предмет: Алгебра,
автор: savikros
b^2/a^2:(a/a-b - a+b/a)
Ответы
Автор ответа:
0
B^2/a^2:(a/a-b - a+b/a)= a+b/a
1. a(a/a-b) - a+b(a+b/a)=a^2-(a+b)(a-b)/a(a-b)=a^2-(a^2-b^2)/a(a-b)=a^2-a^2+b^2/a(a-b)=b^2/a(a-b)
2. b^2/a^2:b^2/a(a-b)=b^2/a^2*a(a-b)/b^2=a-b/a
1. a(a/a-b) - a+b(a+b/a)=a^2-(a+b)(a-b)/a(a-b)=a^2-(a^2-b^2)/a(a-b)=a^2-a^2+b^2/a(a-b)=b^2/a(a-b)
2. b^2/a^2:b^2/a(a-b)=b^2/a^2*a(a-b)/b^2=a-b/a
Приложения:
Похожие вопросы
Предмет: История,
автор: vitaliykhlon223
Предмет: Қазақ тiлi,
автор: ajnurislamova96
Предмет: Другие предметы,
автор: darynka2680509
Предмет: Математика,
автор: енг4
Предмет: Математика,
автор: lmkuzmina2016